Shear behaviour of steel members and beam-to-column joints under elevated temperatures - Qian, Zhenhai (2008)
The objective of current research is to investigate the possibility of using “Component-Based” method to predict steel joint behaviour at elevated temperatures. In this study, the beam web shear component of a joint has first been simplified into an equivalent girder web panel subjected to shear force. Five series of beams have been tested at both ambient and elevated temperatures, without thermal restraints. In addition, three more series of specimens have been tested subjected to thermal restraints at higher temperatures. All plate girders tested at elevated temperatures exhibit web buckling failure mode, similar to ambient temperature tests. A mechanical model for the shear component in present work has been improved from plate theory.